Are community health workers effective in retaining women in the maternity care continuum? Evidence from India. Issue 4 (17th July 2019) - Agarwal, Smisha; Curtis, Sian; Angeles, Gusavo; Speizer, Ilene; Singh, Kavita; Thomas, James
Abstract : Objectives: Despite the recognised importance of adopting a continuum of care perspective in addressing the care of mothers and newborns, evidence on specific interventions to enhance engagement of women along the maternity care continuum has been limited. We use the example of the Accredited Social Health Activist (ASHA) programme in India, to understand the role of community health workers in retaining women in the maternity care continuum. Methods: Using the Indian Human Development Survey data from 2011 to 2012, we assess the association between individual and cluster-level exposure to ASHA and four key components along the continuum of care—at least one antenatal care (ANC) visit, four or more ANC visits, presence of a skilled birth attendance (SBA) at the time of birth and postnatal care for the mother or child within 48 hours of birth, for 13 705 women with a live birth since 2005. To understand which of these services experience maximum dropout along the continuum, we use a linear probability model to calculate the weighted percentages of using each service. We assess the association between exposure to ASHA and number of services utilised using a multinomial logistic regression model adjusted for a range of confounding variables and survey weights. Results: Our study indicates that exposure to the ASHA is associated with an increased probability of women receiving at least one ANC and SBA. In terms of numbers of services, exposure to ASHA accounts for a 12% (95% CI: 9.1 to 15.1) increase in women receiving at least some of the services, and an 8.8% (95% CI: −10.2 to −7.4) decrease in women receiving no services. However, exposure to ASHA does not increase the likelihood of women utilising all the services along the continuum. Conclusions: While ASHA is effective in supporting women to initiate and continue care along the continuum, it does not significantly affect the completion of all services along the continuum.